Chaos Synchronization of Two Different Chaotic Systems via Nonsingular Terminal Sliding Mode Techniques.: Nipaporn Tino, Pimchana Siricharuanun, Chutiphon Pukdeboon - Team, Support (Thai Journal of Mathematics, 2016)
This research studies the problem of finite-time chaos synchronization between two different chaotic systems with uncertain parameters and external disturbances. A nonsingular terminal sliding mode and super-twisting sliding mode control methods are proposed to solve this problem. Based on the Lyapunov stability theory, the proposed control schemes can ensure the finite-time synchronization between the master and the slave chaotic systems under parameter uncertainties and external disturbances. Numerical simulations are presented to demonstrate the applicability and effectiveness of the proposed control techniques.